Smart Tourism: A Holistic Approach for Personalized Tourism Services – Trends, Problems, Possibilities and Projections in Indian Context: Exploring the Role of E-Marketing and Smart Destinations in Uplifting India's Tourism (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Internet has become an essential tool for marketing and promotion globally to reach tourists without any intermediaries. The purpose of e-tourism is to create IT embedded infrastructure at destinations on the one hand and to make traveller smart enough to utilize e-techniques on the other hand. Even after having well established electronic and digital infrastructure, some obstacles come along in the path to reach this goal. UNWTO also emphasizes the overwhelming role of electronic business and commerce in the field of tourism promotion with the objective of attracting more tourists towards various destinations worldwide. As per Ministry of Tourism Report 2018, India’s rank in foreign tourist arrival is 26th worldwide and is able to attract just 1.17 of total tourist traffic in the world. In the aforesaid context, this paper tries to identify issues in relation to FTA in India and how e-marketing strategies along with smart destinations can be utilized play a vital role to uplift India’s rank and share in tourism at global level. In addition, this paper attempts to project the future state of smart tourism in India. In order to draw conclusion and offer suggestions recommendations, researchers employed questionnaire and analyzed secondary data. Secondly, hypothesis testing along with trend analysis was also carried out. In the light of the above statements, results prove e-tourism as a significant and effective tool to promote India tourism and uplift its position at international level.